A highly selective lanthanide-containing probe for ratiometric luminescence detection of an anthrax biomarker. Issue 22 (8th May 2019) - Liu, Xiao; Li, Bin; Xu, Yang; Li, Zhiqiang; Zhang, Ying; Ding, Zhi-Jun; Cui, Hui; Wang, Jing; Hou, Hong-Biao; Li, Huanrong
Abstract : We report a ratiometric luminescent sensor that can identify the Bacillus anthrax biomarker with outstanding selectivity, even including all of the 5 DPA isomers. Abstract : Since anthrax spores are highly lethal to human beings and animals, and also potential biological warfare agents, it is highly desirable to develop simple, robust and easy-device sensors that are rapid and sensitive, and can selectively detect the Bacillus anthrax biomarker dipicolinic acid (DPA) quantitatively. Herein, we report a ratiometric luminescent "turn-on" sensor via mixing Eu 3+ ions, sodium polyacrylate and internal luminescence reference in water, which can identify the Bacillus anthrax biomarker dipicolinic acid (DPA) quantitatively with outstanding selectivity over aromatic ligands and amino acids, even including all of the 5 DPA isomers.